2013
DOI: 10.1109/tlt.2013.18
|View full text |Cite
|
Sign up to set email alerts
|

A Software Suite for Efficient Use of the European Qualifications Framework in Online and Blended Courses

Abstract: Since introduction of the European qualifications framework (EQF) as one instrument to bridge from learning institutions to competence driven lifelong learning, it remains a challenge for instructors and teachers in higher education to make efficient use of this framework for designing, monitoring, and managing their lessons. This paper presents a software suite for enabling teachers to make better use of EQF in their teaching. The software suite extends course design based on well-defined learning outcomes, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 13 publications
0
25
0
2
Order By: Relevance
“…Although most of the studies were not in the space of digitally mediated learning, we found a few studies, such as those by Di Mitri et al . ( 2017 ) and Florian-Gaviria et al . ( 2013 ), that focused on blended and online learning, respectively.…”
Section: Learning Environment and Pedagogical Approachmentioning
confidence: 95%
See 1 more Smart Citation
“…Although most of the studies were not in the space of digitally mediated learning, we found a few studies, such as those by Di Mitri et al . ( 2017 ) and Florian-Gaviria et al . ( 2013 ), that focused on blended and online learning, respectively.…”
Section: Learning Environment and Pedagogical Approachmentioning
confidence: 95%
“…Second, research has considered both sides of instruction: for students by predicting their learning task performance (Kaklauskas et al ., 2015 ) and for teachers in order to understand their classroom orchestration strategies and needs (Prieto, Sharma, Dillenbourg, & Jesús, 2016 ;Prieto et al ., 2018 ). Third, researchers have focused on the learning scenarios: face-to-face, to understand how teachers manage the classroom (Prieto et al ., 2016(Prieto et al ., , 2018 and online learning scenarios, to predict students' learning-task performance (Florian-Gaviria, Glahn, & Gesa, 2013 ).…”
Section: Practitioner Notesmentioning
confidence: 99%
“…Based on decision given by authentication system, the authorization follows the users or system.In order to access the resource, identity of the users is monitored. Confidentiality [15] is the main factor of security services in untrusted communication networks.Encryption mechanisms are mainly deployed for securing the data.The fig.2.2 presents the security model of the e-learning portals.…”
Section: Security In Web-learning Systems and Resultsmentioning
confidence: 99%
“…Learners can monitor themselves (self-monitoring) or learners can be monitored by another person, usually by a teacher or an administrator. Monitoring can be activity-centred (process) or outcome-centred (product) (Florian-Gaviria et al, 2013). Monitoring can take place in real-time or post-hoc.…”
Section: Monitoring Awareness and Reflectionmentioning
confidence: 99%
“…Among the rest, there were two studies performing controlled or usability evaluations (in the case of Park & Jo (2015), to complement an authentic setting evaluation), and two other studies only reported evaluations informally. The scale and duration of the system evaluations performed in authentic settings was relatively uniform: 13 out of the 14 authentic setting evaluation studies gathered data from students (ranging from n students = 11 to n students = 300, mean value of n students = 93, with a standard deviation of σ = 78.5); on the other hand, 10 of these 14 studies involved teachers in the evaluation (normally, between one and four of them, with the exception of Florian-Gaviria et al (2013), in which n teachers = 20). All of the authentic setting evaluations were performed over one to three courses, and the length of the interventions ranged from one week to a full semester (per course).…”
Section: Action-related (34)mentioning
confidence: 99%